Monitoring of the visitors impact at “Ponta da Ferraria e Pico das Camarinhas” geosite (São Miguel Island, Azores UNESCO Global Geopark, Portugal) - Lima, Ana (2017)
"Ponta da Ferraria e Pico das Camarinhas" is a protected geosite in São Miguel Island in the Azores archipelago, Portugal. Due to its importance for the geoconservation strategy of the Azores UNESCO Global Geopark, monitoring actions of visitor impact were implemented in order to assure that the main geological features of this geosite continue to be in a favourable status of conservation, taking into account present public use. Different types of data were collected over a one-year period aiming at the identification of factors that may affect the geosite and also the assessment of the eventual decrease of relevance that this geosite has experienced throughout that period. Among the many geological features that occur in the geosite, the littoral cone (or pseudocrater) was considered the most threatened due to its uniqueness and high vulnerability. The number of visitors was also analysed with respect to the geosite’s carrying capacity. The monitoring of this geosite allowed the definition of practical actions, in par- ticular to be addressed to the governmental agency who is responsible for the management of this geosite.